Transformation pathway and toxicity assessment of malathion in aqueous solution during UV photolysis and photocatalysis. (November 2019) - Li, Wei; Zhao, Yao; Yan, Xiaoqing; Duan, Jinming; Saint, Christopher P.; Beecham, Simon
Abstract: In drinking water treatment, complete mineralization of organophosphorus pesticides (OPPs) by UV-based advanced oxidation processes (UV AOPs) is rarely achieved. The formation of intermediate oxidation byproducts would likely have some profound effects on toxicity of the reaction solutions. This study investigated the intermediate oxidation byproducts, transformation pathway and toxicity of malathion solutions during the treatment processes of UV alone, UV/H2 O2, UV/TiO2 and UV/Fenton. The main intermediate oxidation byproducts were derived using ultra-performance liquid chromatography - electrospray - time-of-flight mass spectrometry. Thereby the transformation pathway for each of these treatment processes was proposed. The results indicate that in UV photolysis, the transformation pathway of malathion proceeded initially via cleavage of the phosphorus-sulfur bonds while in photocatalysis, the desulfurization from a PS bond to a PO bond was the primary degradation pathway. Interestingly, only in the UV/TiO2 process a small fraction of malathion was found decomposed via a demethylation reaction. At the same time, a toxicity assessment of the treated solutions was conducted by both luminescence inhibition of Vibrio fischeri and inhibition of acetylcholinesterase (AChE). It was found that after UV AOP treatment, the toxicity of the malathion aqueous solution increased sharply. In contrast, no increase in toxicity was observed for the malathion aqueous solution after UV alone treatment. This study demonstrates that the high removal efficiency achieved by OPPs does not imply that detoxification of the water solution has been achieved. On the contrary, the toxicity of the treated solutions by OPPs may be increased significantly depending on the selected treatment processes. Graphical abstract: Image 1 Highlights: UV and UV AOPs followed different pathways during degradation byproduct formation. Toxicity of malathion solution treated by UV AOPs increased with removal efficiency. Toxicity of malathion solution was relatively unchanged during UV alone treatment. Formation of malaoxon contributed to AChE toxicity but not to acute toxicity.